Effect of demographic factors on attitudes to purchase children’s supplement products - Safaria, Triantoro; Hidayah, Nurul; Aulia, Aulia (International Journal of Public Health Science (IJPHS), 2024)
Children's supplements are products widely offered by drug manufacturers. Their benefits and uses are essential for supporting the growth and health of children. Nevertheless, there is a lack of research in Indonesia examining the relationship between parental demographic factors and attitudes towards purchasing children’s supplements. This study employs a mixed-method approach to investigate the impact of demographic factors on attitudes toward purchasing children’s supplement products, aiming to fill the research gap. A total of 124 parents from diverse backgrounds participated as respondents, with 29.8% being male and 70.2% female. Their education levels ranged from high school (7.3%), bachelor’s degree (26.6%), master’s degree (50%), to doctoral degree (16.1%). The results of the regression analysis indicate that only income level plays a positive role in shaping attitudes towards purchasing children’s supplements. Notably, 89.5% of respondents believe in the benefits of these supplements. This study highlights the influence of income level on buying attitudes regarding children’s supplements. Future research should consider a larger sample size to better represent the population.